FAKTOR YANG MEMPENGARUHI MASYARAKAT DALAM MENYALURKAN ZAKAT, INFAK, SEDEKAH MELALUI PLATFORM CROWFUNDING - Prysca Anggita Putri; Aan Zainul Anwar (Universitas PGRI Semarang, 2021)
This study aims to find out the factor religious, campaign, platform innovation, accesbility, and environment toward the distribution of zakat, infka, alms, through online. This research use descriptive quantitative method, with multiple linear regression test tools. Data obtained through questionnaires and observation from digital media users who milk to distribute zakat, infak, alms through online. Factors studied include; religiosity, campaign, platform innovation, accessibility and the environment. The result of this study show religiosity, campaign, and accessibility have a positive and significant effect on the distribution of zakat, infak,alms online. Platform innovation have a positive and insignificant effect and the environment has no effect on the distribution of zakat, infak, alms onlineAbstract